2002
DOI: 10.1177/016235320202600103
|View full text |Cite
|
Sign up to set email alerts
|

Gifted Black Males in a Predominantly White University: Portraits of High Achievement

Abstract: This article addresses the limited research on high-achieving African American students by examining the experiences of 5 gifted Black males in a predominantly White university setting. Through case study research methodology, this study revealed significant factors that influenced the achievement of the gifted university males. Themes uncovered in the data included influential mothers, recognition of giftedness, and support from significant teachers and mentors. These factors interacted to shape a belief in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…They described how the availability of support programs assisted them in gaining the skills and ultimately the confidence they needed to achieve their academic goals. Similar to the studies by Williamson (2010) and Hébert (2002), Flowers' (2012) research revealed that family was a major resource for students. And much like the men in Herndon's (2003) work, many of these men expressed a strong spiritual base, acknowledging the role God played in their academic talent.…”
Section: Black Male Success At Historically Black Colleges and Universupporting
confidence: 56%
See 3 more Smart Citations
“…They described how the availability of support programs assisted them in gaining the skills and ultimately the confidence they needed to achieve their academic goals. Similar to the studies by Williamson (2010) and Hébert (2002), Flowers' (2012) research revealed that family was a major resource for students. And much like the men in Herndon's (2003) work, many of these men expressed a strong spiritual base, acknowledging the role God played in their academic talent.…”
Section: Black Male Success At Historically Black Colleges and Universupporting
confidence: 56%
“…The study investigated how Black males perceive their own levels of academic achievement, what relationships they found most supportive, and the impact of the campus on their successes and failures. Comparable to the participants in Williamson's (2010), and Strayhorn's (2008) studies, the men in Hébert's (2002) study identified family and an integrated support group as factors positively influencing their academic success. These young men also revealed that their talents were recognized at an early age and nurtured by a mentor, often beginning in elementary school and persisting through postsecondary education, a factor that assisted in the cultivation of self-efficacy.…”
Section: Black Male Success At Predominantly White Institutionsmentioning
confidence: 78%
See 2 more Smart Citations
“…Their counter narratives invalidate subversive stereotypes. The proliferation of such counter narratives hinges on establishing and maintaining academic environments in which gifted African American males find and develop their racial identity, self-esteem, and sense of self-efficacy (Hébert, 2002). Whiting (2006), building upon Bandura's (1977Bandura's ( , 1986) theory on selfefficacy, further establishes self-efficacy as the linchpin in the development of one's identity, specifically scholar identity.…”
Section: Introductionmentioning
confidence: 99%